Impact of infertility on marital relationships among infertile couples attending OPD of a tertiary health care centre - Kushwaha, Chhaya; Sinha, Parul; Gupta, Uma; Srivastava, Kumkum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There is little empirical literature on the effects of infertility on marital relationships in India. This study was sought to examine the impact of infertility on the marital relationships of the couple at Eras Lucknow Medical College and Hospital. Methods: This is a descriptive cross-sectional design conducted on infertile women presenting in OPD (outpatient department) of Obstetrics and Gynecology Department of Era’s Lucknow Medical College and Hospital. A self-developed questionnaire was used for collecting data for the study. The questionnaire was divided into 5 sections: A to E. Data was presented in the form of descriptive statistics such as proportion and percentage. Results: This study revealed that infertility affected the sexual life of participants as it was reported that even though they still had regular sexual intercourse with their partners after realising they were infertile (64.5%), sex was only for the purpose of reproduction and not for mutual sexual satisfaction (13%). Sexual intercourse was reported to be unfulfilling as well as unenjoyable (16.4%). The psychological well-being of participants (29.60%) and stability within marital unions were also negatively affected by infertility, resulting in quarrels (13 %). Conclusions: Infertility has numerous negative implications for marital relationship. Thus, infertile persons should not be only physically examined and treated for infertility but should also be given counselling to lessen the psychological trauma attached to infertility.